Porous Sandwiched Graphene/Silicon Anodes for Lithium Storage. (1st March 2017) - Wei, Liangming; Hou, Zhongyu; Wei, Hao
Highlights: In situ hydrolysis of tetraethoxysilane within the confined galleries region of graphite oxide. New porous sandwiched graphene/Si nanocomposites were prepared by magnesium thermal reduction. The Si nanostructure was compactly sandwiched between two neighboring graphenes. The Si/graphene anodes deliver large reversible capacity with excellent cycling stability. Abstract: Porous sandwiched graphene/Si nanocomposites (PG-Si) are prepared by in situ hydrolysis of tetraethoxysilane within the confined gallery region of graphite oxide, and then magnesium thermal reduction of the intra-gallery SiO2 to Si nanocrystals. The Si nanostructures are in situ formed within the confined gallery region of graphite, and they are compactly sandwiched between two neighboring graphene sheets. This compactly sandwiched structure affords enhanced electron conductivity, and prevents Si nanoparticles from aggregation. Meanwhile, the free voids between neighboring Si nanocrystals alleviate the volume change of Si during cycling. As a consequence, the resulting PG-Si nanocomposites are high-performance anode materials for lithium-ion batteries which show long cycle life (>500 cycles) and high specific charge capacity (1464 mAh g −1 at a current density of 200 mA/g, 920 mAh g −1 at a current density of 1.68A/g after 500 cycles). The Li + diffusion kinetics in PG-Si is also discussed.